Analysis of the Evaporation Method to Obtain Soil Thermal Conductivity Data in the Full Moisture Range. Issue 2 (8th April 2016) - Markert, Arvid; Peters, Andre; Wessolek, Gerd
Abstract : Core Ideas: Implication of the evaporation method for high‐resolution λ measurements over the full moisture range. Impact of the evaporation process on the estimation of λ is negligible. High heating powers reduce substantially the random variation of the λ(θ)‐data. Single heat probe measurements were combined with the evaporation method to obtain thermal conductivity (λ) data covering the whole soil moisture range from saturation to air‐dryness. Measurements were performed under low, medium, and high heating modes to analyze the effect of applied heating power. To analyze the effect of heat transport due to evaporation on measured λ, evaporation rate was reduced by covering the soil column in predefined time intervals. Three different soils, including a sand, a sandy loam, and a silt loam were used to examine the effectiveness and validity of this combined technique. Results show that the accuracy of the thermal conductivity measurements depends on (i) heating power, (ii) soil texture, and (iii) soil moisture. The random variation of measured λ was high for low heating power but clearly reduced with increasing heating power. Systematic variations of λ between the three applied heating modes were negligible for the sandy loam and silt loam over the complete moisture range. No systematic effect of heating mode was found for the sand at medium to high water contents, whereas a clear effect was found at low soil moisture. The evaporation process had a slight, but negligible effect on λ‐measurements. From our findings we suggest using a high heating power for medium‐ and fine‐textured soils throughout the measurement. For coarse materials, the heating power should be high for high water contents and reduced when water contents become low. The evaporation method is a powerful and easy‐to‐use application to obtain highly resolved soil thermal conductivity data over the full moisture range.